The influensce of adiponectin on the occurrence of metabolic disorders in children with overweight and obesity - H.A. Pavlyshyn; K.V. Kozak (Bukovynian State Medical University, 2019)
The results of study of the relationship of adiponectin and basic metabolic disorders in children with overweight and obesity aged 10-17 years were showed in the article. Hypoadyponektinemia is typical for all children with overweight and obesity. Adiponectin has a positive effect on carbohydrate and lipid metabolism by reducing of effects of insulin resistance, hyperinsulinemia, and antiatherogenic effect (reduction the level of total cholesterol, serum low-density lipoprotein, non-HDL-cholesterol and atherogenic coefficient).